VD_FINDINFO Arrêt / 2024 / 646 vom 12. August 2024 - VD Tribunal cantonal (2024)
ÉVALUATION DE L'INVALIDITÉ, REVENU D'INVALIDE, REVENU SANS INVALIDITÉ, FORCE PROBANTE | 28 al. 1 LAI, 28 al. 2 LAI, 6 LPGA, 7 LPGA, 8 al. 1 LPGA